2014
DOI: 10.5935/0103-507x.20140027
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for prevention of acute kidney injury in cardiac surgery: an integrative review

Abstract: Acute kidney injury is a common complication after cardiac surgery and is associated with increased morbidity and mortality and increased length of stay in the intensive care unit. Considering the high prevalence of acute kidney injury and its association with worsened prognosis, the development of strategies for renal protection in hospitals is essential to reduce the associated high morbidity and mortality, especially for patients at high risk of developing acute kidney injury, such as patients who undergo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
(76 reference statements)
3
5
0
1
Order By: Relevance
“…33 It provides oxygenated and decarboxylated blood, retains the native pulsatile cardiac output thus the impact of alterations upon hemodynamics and renal perfusion may be less. 6 Several recent studies have shown that pulsatile flow may provide more beneficial and protective effects on renal microcirculation and perfusion than non-pulsatile flow, 32, 34, 35 and these findings are consistent with the differences identified between the working flows of different types of ECMO. Considering these indications, the beneficial effects of VV ECMO may be related to the early correction of blood gas disturbances, enhanced systemic oxygenation and reduced oxygen consumption (which may improve the renal metabolism) 36 whereas VA ECMO restores adequate end-organ perfusion during low cardiac output in myocardial infarction, end-stage or refractory heart failure, worsening congestion, and cardiogenic shock, which is considered a trigger for AKI (type-1 cardiorenal syndrome).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…33 It provides oxygenated and decarboxylated blood, retains the native pulsatile cardiac output thus the impact of alterations upon hemodynamics and renal perfusion may be less. 6 Several recent studies have shown that pulsatile flow may provide more beneficial and protective effects on renal microcirculation and perfusion than non-pulsatile flow, 32, 34, 35 and these findings are consistent with the differences identified between the working flows of different types of ECMO. Considering these indications, the beneficial effects of VV ECMO may be related to the early correction of blood gas disturbances, enhanced systemic oxygenation and reduced oxygen consumption (which may improve the renal metabolism) 36 whereas VA ECMO restores adequate end-organ perfusion during low cardiac output in myocardial infarction, end-stage or refractory heart failure, worsening congestion, and cardiogenic shock, which is considered a trigger for AKI (type-1 cardiorenal syndrome).…”
Section: Discussionsupporting
confidence: 70%
“…The copyright holder for this this version posted March 30, 2020. ; https://doi.org/10.1101/2020.03.25.20043950 doi: medRxiv preprint hemodynamics and renal perfusion may be less [6]. Several recent studies have shown that pulsatile flow may provide more beneficial and protective effects on microcirculation and renal perfusion than non-pulsatile flow [34][35][36], these findings were consistent with the difference of the working flow between modes of ECMO. In addition, the enhanced systemic oxygenation and reduced oxygen consumption may improve the renal metabolism in VV ECMO [39].…”
Section: Discussionsupporting
confidence: 60%
“…Conversely, VV-ECMO maintains pulsatile cardiac output, and alterations in renal perfusion may conceivably be smaller [4]. Recent studies have shown that pulsatile flow may provide beneficial effects over non-pulsatile flow, especially protective effects on microcirculation and renal perfusion [88,89,90]. The differences in patient population and pulsatility between the two types of ECMO are likely explanations underlying the higher AKI incidence among patients requiring VA-ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Serial measurements of cystatin C levels enable clinicians to identify renal failure in early stages in the postoperative period. 13 Thus, preoperative determination of possible predictors is of the utmost importance in identification of such patients preoperatively. [12][13][14][15][16][17][18] Prolonged duration in ICU or in hospital due to AKI is also associated with the increase in utilization of resources, 13 mostly in elderly patients who undergo CABG under CPB and are at a particularly Therefore, early detection of developed AKI is very important for effective prevention and treatment during postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…10 Serum cystatin C (CysC) is a newly identified marker of renal function. Cystatin C is a lowmolecular-weight protein (13,359 Da) that is produced by all nucleated cells at a constant rate, released into the bloodstream, freely filtered by the renal glomeruli, and catabolized in the proximal tubules. 10,11 Neutrophil gelatinase-associated lipocalin (NGAL) is a small 25-kDa glycoprotein secreted by activated neutrophils.…”
Section: Abstract: Acute Renal Injury -Elderly Patients -Renal Biomamentioning
confidence: 99%